THE EFFECTS OF MAGNETIC VECTOR POTENTIALS ON ABSORBING POLARIZED LIGHT IN A TWO-DIMENSIONAL ELECTRON GAS - Jindanate, Suphawich; Amthong, Attapon (PSRU Journal of Science and Technology, 2024)
In this work, a two-dimensional electron gas system under a uniform magnetic field is studied. This field is described by three vector potentials: Symmetric gauge, Landau gauge X and Landau gauge Y. The aim of this research is to compare the optical properties calculated using these three vector potentials. After solving the Schrödinger equation analytically, it is found that using all three vector potentials results in positive oscillator strengths for energy absorption and negative oscillator strength values for energy emission. In addition, it is found that the light absorption coefficients calculated from these three vector potentials are identical; the highest values of the absorption coefficients exhibit a blue shift behavior when the magnetic field increases. However, the absorption coefficients from these three vector potentials can be calculated at particular different angles of polarized light. This study provides an understanding of the behavior of each form of vector potentials that affects the optical properties, which can be used to select the appropriate vector potentials for other interested systems. It can also be applied in the design of controlling the optical properties of modern electronic devices by tuning magnetic fields.